Empowering Community Health Worker to Reduce Stunting Among Toddlers: Systematic Review - Putra, Mepsa; Rekawati, Etty; Permatasari, Henny; Sari, Indah Permata (jitek, 2024)
Introduction: Stunting is a chronic nutritional disorder in toddlers that inhibits growth and development. There are several efforts to prevent and overcome stunting, one of which is empowering Community Health Workers. Objective: This research will identify the research results regarding the effect of empowering Community Health Workers on reducing stunting in toddlers. Method: This research uses a Systematic Review methodology by searching for articles from PubMed, ScienceDirect, Scopus, Clinical Key, and ProQuest. The article search technique uses the PRISMA method. Results: 7 suitable articles were found, which prove that the Community Health Workers approach influences reducing stunting in toddlers. Conclusion: Empowering health workers can be used as a community-based approach to reducing stunting.